Sociodemographic and Nutritional Profile of Oncological Patients in Enteral Nutritional Therapy - Bortoletto, Michelle Martins (2018)
Introduction: Cancer patients are at high nutritional risk, with malnutrition and cachexia being commonly observed in these individuals. Enteral nutritional therapy (ENT) is a therapy that can offer numerous benefits for these. Objective: To identify the sociodemographic and nutritional profile of cancer patients, relating to the effects of ENT with nutritional status and clinical evolution of these patients. Method: Retrospective clinical study with review of electronic medical records of patients admitted from September 2016 to April 2017 at a public and private oncology hospital in the city of Juiz de Fora - MG. Statistical analyzes were by means of frequencies and proportions and means and standard deviations depending on the variables, being p <0.05. Results: Among 96 charts analyzed, 68.75% were males, 54.16% were elderly, 52.1% were former smokers, 39.6% were ex- and 46.9% had head and neck cancer. Of these, 44.8% were suspected of malnutrition and 39.6% were malnourished. The mean BMI was 19.44 ± 4.83 kg / m² and the weight was 52.91  ± 12.97 kg before the ENT and 18.76 ± 4.47 kg / m² and 51.01 ± 12.69 kg after seven days in ENT, showing no significant difference between the values obtained before and after ENT. The classification of the percentage of weight loss at the beginning of ENT showed 88.5% with severe weight loss and after seven days of therapy there was a reduction in this percentage to 46.9%. Conclusions: Most cancer patients present with progressive impairment of nutritional status. ENT was a therapy that contributed positively to the delay of weight loss in these patients.